?WHEAT (TRITICUM AESTIVUM L.) STAND ESTABLISHMENT IN LEGUME AND NON-LEGUME BASED CROPPING SYSTEMS (Biological Sciences - PJSIR, 1998)
Wheat stand establishment behaviour was studied in different cropping systems under rainfed conditions, during 1992- 94. On the basis of wheat emergence (rn") and emergence rate index, two distinct groups of cropping systems were observed. The first group included fallow-wheat, mashbean-wheat, mungbean-wheat and cowpea-wheat systems whereas the second included maize-wheat, sorghum-wheat, millet-wheat, sunflower wheat and soy bean-wheat systems. Wheat stand establishment was significantly (P